Nephrocalcinosis in farmed salmonids: diagnostic challenges associated with low performance and sporadic mortality - Minarova, Hana; Palikova, Miroslava; Kopp, Radovan; Maly, Ondrej; Mares, Jan; Mikulikova, Ivana; Papezikova, Ivana; Piacek, Vladimir; Pojezdal, Lubomir; Pikula, Jiri (Frontiers in Veterinary Science, 2023)
Disease conditions that involve multiple predisposing or contributing factors, or manifest as low performance and/or low-level mortality, can pose a diagnostic challenge that requires an interdisciplinary approach. Reaching a diagnosis may also be limited by a lack of available clinical profile parameter reference ranges to discriminate healthy fish from those affected by specific disease conditions. Here, we describe our experience investigating poorly performing rainbow trout (Oncorhynchus mykiss) in an intensive recirculation aquaculture, where reaching a final diagnosis of nephrocalcinosis was not as straightforward as one would wish. To list the issues making the diagnosis difficult, it was necessary to consider the creeping onset of the problem. Further diagnostic steps needed to ensure success included obtaining comparative data for fish blood profiles and water quality from both test and control aquacultural systems, excluding infections with salmonid pathogenic agents and evaluating necropsy findings. Major events in the pathophysiology of nephrocalcinosis could be reconstructed as follows: aquatic environment hyperoxia and hypercapnia → blood hypercapnia → blood acid-base perturbation (respiratory acidosis) → metabolic compensation (blood bicarbonate elevation and kidney phosphate excretion) → a rise in blood pH → calcium phosphate precipitation and deposition in tissues. This case highlights the need to consider the interplay between water quality and fish health when diagnosing fish diseases and reaching causal diagnoses.